Ideologi dan Kekuasaan dalam Iklan Mobil Honda ”All New City” - Nuryanti, Dewi (ESENSI LINGUA, 2023)
This research aims to explain how advertisers of a product attempt to convey the ideology present in Honda car advertisements and the power they intend to emphasize through those ads. Additionally, the study seeks to understand the reasons behind the advertiser's choice of positioning in the advertisement. Data were collected from advertisements in the Kompas newspaper. The theories employed in this research include those by Cook, Fairclough, and Barthes. The results of the analysis indicate that the advertiser prioritizes the positioning in this ad by focusing on the interior of the car, highlighting the luxury offered to buyers. The power in this advertisement is demonstrated by the use of the color red, which not all advertisers employ, making it a distinctive feature of this product that is not found in others. Meanwhile, the ideology presented by the advertiser is that only with the Honda "All New City" product, every buyer or user can achieve all their dreams, unlike with other products. With this product, individuals from different social status can enjoy luxury without having to buy an expensive product. This is because the product promises luxury for all societal layers, whether they are affluent or economically ordinary, they will still experience luxury through this product.